2018
DOI: 10.1177/1049731518792309
|View full text |Cite
|
Sign up to set email alerts
|

Functional Family Therapy (FFT) for Behavior Disordered Youth Aged 10–18: An Overview of Reviews

Abstract: Purpose: This overview of reviews analyses the existing evidence base of functional family therapy (FFT), which is a manualized, family-based intervention for youth with behavioral problems and their families. FFT has been implemented among youth aged 10–18 at risk of, or presenting with, behavioral problems such as delinquency, violence, substance abuse, sexual perpetration, and truancy. Method: A multipronged search was conducted across 15 databases, 10 websites, and expert contacts in February 2018. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 55 publications
1
26
0
Order By: Relevance
“…None of the aforementioned studies measured school‐related behaviors (e.g., school performance, skipping school), which neglects an important dimension related to adolescent delinquency. A recent meta‐analysis of 31 FFT literature reviews between 1986 and 2018 stated that there were no school‐related outcomes reported in any of the articles examined (Weisman & Montgomery, ). Thus, a larger study with a broader set of outcomes is necessary to more fully examine the potential effectiveness of FFT within an international context, specifically in Denmark.…”
Section: Family Therapymentioning
confidence: 99%
“…None of the aforementioned studies measured school‐related behaviors (e.g., school performance, skipping school), which neglects an important dimension related to adolescent delinquency. A recent meta‐analysis of 31 FFT literature reviews between 1986 and 2018 stated that there were no school‐related outcomes reported in any of the articles examined (Weisman & Montgomery, ). Thus, a larger study with a broader set of outcomes is necessary to more fully examine the potential effectiveness of FFT within an international context, specifically in Denmark.…”
Section: Family Therapymentioning
confidence: 99%
“…Additional social service and victim cost savings are associated with reduced recidivism. Consistent with the larger body of research on FFT, Weisman and Montgomery (2018) report that, compared to alternative treatment, FFT was shown to have “modest” reductions in youth reoffending (28% in FFT vs. 57% in alternative treatment), modest effects on youth substance use, and modest effects on secondary outcomes. Despite these positive results, they claim that FFT might be harmful to youth and families, and they call for suspending implementation efforts.…”
mentioning
confidence: 59%
“…An extension of systematic reviews is the overview of reviews approach in which the source material is review articles, including meta-analyses, rather than original research articles (Weisman & Montgomery, 2018). We recognize the potentially important role that high-quality review of reviews can play in understanding RSIs but also recognize the quality of these reviews may be compromised for various reasons.…”
Section: Strengths and Limitations Of Review Of Review Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to understand and identify the elements of the intervention which are working and result in positive outcomes, and possible areas that require modification or adaptation. Recent overview and meta-analytic evidence illustrates the variability in core outcomes, thus confounding any certainties regarding the implementation and usage of FFT with such a heterogenous population and across varied settings (Weisman & Montgomery, 2018;Hartnett et al, 2017).…”
Section: Methodsmentioning
confidence: 99%